Role of Clustering in Economic Growth and Entrepreneurship Activity: The Comparative Study in Case of Bursa and Konya Industrial Clusters - Karakayaci, Ozer (YILDIZ TECHNICAL UNIV, FAC ARCHITECTURE, 2010)
The academic discourse in economic geography, regional science, and economic sociology has been characterized over the last three decade by two key concepts: entrepreneurship as the creation of new organizations and clusters as a source of competitiveness and cooperation. The literature is a matter of opinion that entrepreneurship activity is one key element of local and regional development when concepts such as entrepreneurship, clustering and economic growth are concerned essentially with an extensive literature of on the subject such as economic geography, regional science and sociology. Entrepreneurial activities and behaviors are considered to be the starting point clustering tendencies describing as social atmosphere due to geographically concentration and institutionalization to particular region of firms. In this context, possible effects for entrepreneurs activity and regional economic development of industrial clusters' social and economic aspects have been been an intense debate on the theoretical aspects. For this reason, the study has been focused on the possible effects of economic growth and entrepreneurs' activity/behavior in industrial clusters. The aim of the study, regions clustering in terms of the manufacturing industry has determine the role of clustering being possible effects of economic growth and entrepreneurs activity/behavior. In this context, regions clustered and clustering in terms of the manufacturing industry have been comparatively analyzed possible effects clustering on economic growth and entrepreneurs' activity/behavior. The study followed a two-stage method. The first stage, location quotient are analyzed in the light of variables such as firm size data and number of firm. After location quotient had been completed, the concentration level of regions in terms of manufacturing industry was determined. The second stage, industrial clusters impacted on economic growth and entrepreneur activity/behavior have been analyzed as a statistical in light of the data obtained from field work and secondary sources in clustered and clustering regions in terms of the manufacturing industry. This study attempt to explain whether the regions displaying the clustering tendencies in manufacturing are more prosperous than the regions where the manufacturing firms are geographically dispersed.
Keywords: Entrepreneurial activity; entrepreneurial behavior; industrial clusters; economic growth; Architecture